«Nord stream-2» as a mechanism of Russian economic influence on the policy of the European States - Kravchenko, Olha (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article analyzes political aspects of construction Russian pipeline Nord Stream-2 and its influence on relations between EU member states and the Russian Federation. During the research, it was in detail analyzed the impact of the Russian capital on the process of foreign policy decision making by European governments. The article proves, that the Russian pipeline Nord Stream-2 is not economic, but the politically motivated project. The subject of research of the article is increasing the dependence of EU member-states from Russian influence as a result of construction Nord Stream 2, which is one of the elements of the hybrid policy of the Russian Federation, aimed against EU and NATO member states. The purpose of the article is to analyze the mechanism of the Russian energy influence on the policy of the European states, to reveal threats for the energy security of the European continent, and the impact of economic ties on policy-making of the states regarding Russian aggressive policy. The research describes, how Russia enhances the dependence of European states from natural gas and oil supplies, that appears in the strengthening of Russian political role in Europe. Special attention is paid to the impact of Nord Stream-2 on French and German position on Russia`s military aggression against Ukraine. This research allows in detail to study the problem, to analyze threats in purpose to develop an effective mechanism of countering this energy threat. The research activity of this nature may be useful for forming the strategy of saving the status of the transit state of Ukraine and the development of the dialogue with partner states in the context of the construction of the security system and countering Russian influence.